2006
DOI: 10.1107/s1600536806013687
|View full text |Cite
|
Sign up to set email alerts
|

6-(4-Chlorophenyl)imidazo[2,1-b][1,3,4]thiadiazole-2-sulfonamide

Abstract: Key indicatorsSingle-crystal X-ray study T = 291 K Mean (C-C) = 0.004 Å R factor = 0.037 wR factor = 0.102 Data-to-parameter ratio = 11.5For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…41 Even though the dispersion of these parameters over the compared structures, in particular the HÁ Á ÁN1 distance, as well as the R wp figure of merit, are slightly smaller in the case of the Etho_dA model compared with Etho_uB, they still cannot be taken as clear evidence for the fact that the A supra-molecular arrangement would provide a better picture for the actual ethoxzolamide structure. Stronger arguments for such a conclusion are provided instead by a comparison with the data reported in literature on similar sulfonamide containing compounds: [43][44][45][46][47][48][49][50][51] specifically, in all of the analyzed cases it was found that the hydrogen bonding pattern around the -NH 2 moiety corresponds to the supra-molecular arrangement in Fig. 2A.…”
Section: Quantum Mechanical Geometry Optimizationmentioning
confidence: 92%
“…41 Even though the dispersion of these parameters over the compared structures, in particular the HÁ Á ÁN1 distance, as well as the R wp figure of merit, are slightly smaller in the case of the Etho_dA model compared with Etho_uB, they still cannot be taken as clear evidence for the fact that the A supra-molecular arrangement would provide a better picture for the actual ethoxzolamide structure. Stronger arguments for such a conclusion are provided instead by a comparison with the data reported in literature on similar sulfonamide containing compounds: [43][44][45][46][47][48][49][50][51] specifically, in all of the analyzed cases it was found that the hydrogen bonding pattern around the -NH 2 moiety corresponds to the supra-molecular arrangement in Fig. 2A.…”
Section: Quantum Mechanical Geometry Optimizationmentioning
confidence: 92%
“…Due to increasing interest towards understanding these interactions in solids, quantitative investigation of these interactions using various computational tools provides a platform for evaluating the role of different atom contacts that contribute towards crystal packing. [9][10][11]…”
Section: Introductionmentioning
confidence: 99%